2004
DOI: 10.1086/422571
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis, Reionization, and the Mass Function of the First Stars

Abstract: We critique the hypothesis that the first stars were very massive stars (VMS; M > 140 Msun). We review the two major lines of evidence for the existence of VMS: (1) that the relative metal abundances of extremely metal-poor Galactic halo stars show evidence of VMS enrichment, and (2) that the high electron-scattering optical depth (tau_e) to the CMB found by WMAP requires VMS for reionization in a concordance LambdaCDM cosmology. The supernova yield patterns of VMS are incompatible with the Fe-peak and r-proce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
158
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 75 publications
11
158
1
Order By: Relevance
“…However, despite these strong links between globular clusters and SSCs, we do not know how the extremely low metallicity in the early universe affected massive star cluster formation. A low metal content may affect star formation in a variety of ways, including cooling and pressure in the birth cloud, hardness of the stellar spectra, and evolution of the stars themselves (e.g., Schaerer 2002;Smith et al 2002;Tumlinson et al 2004;Bate 2005). One way to approach this question is to study SSC formation in extremely low-metallicity systems in the local universe.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these strong links between globular clusters and SSCs, we do not know how the extremely low metallicity in the early universe affected massive star cluster formation. A low metal content may affect star formation in a variety of ways, including cooling and pressure in the birth cloud, hardness of the stellar spectra, and evolution of the stars themselves (e.g., Schaerer 2002;Smith et al 2002;Tumlinson et al 2004;Bate 2005). One way to approach this question is to study SSC formation in extremely low-metallicity systems in the local universe.…”
Section: Introductionmentioning
confidence: 99%
“…As these stars produced heavier elements, the universe achieved a critical metallicity (∼ 10 −4 times solar metallicity) [4], at which point the massive mode of star formation yielded to a more normal distribution of stellar masses with a SFR peaked at z ≈ 3. A more detailed understanding of the first epoch of star formation will rely on the phenomenological consequences of the models such as element enrichment and supernova rates [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, using those yields, Tumlinson et al (2004) have shown that it provides only a very poor fit to the abundances pattern observed in the metal-poor stars known today. The odd-even effect is not observed, and the models significantly over-produce Cr and under-produce V, Co and Zn.…”
Section: A Typical Chemical Signature Which Remains Unobservedmentioning
confidence: 99%